Ensayo uniforme de Rendimiento de 13 líneas y 03 variedades de Arroz (Oryza sativa L.) Bajo riego en Nueva Cajamarca región San Martin - Torres Panduro, Edwin (1997)
This trial was conducted at the Agricultural Experimental Station Nueva Cajamarca district of the same name, Rioja Province and Department of San Martin - Peru, between 6 ° 08¡de south latitude and 76 ° 50' west longitude and altitude 850 m. The objective was to evaluate and select 16 lines and varieties for performance, milling quality and other characteristics related to productivity, of which 13 are experimental lines from Colombia (CIAT) and 3 are commercial varieties (Uquihua, Alto Mayo and High Forest ). The experimental design was the randomized Fully block with three replicates and mean significance test was Duncan (a = 0.05). The seedbed for both lines studio and witnesses settled on 30 June 1995, using the system dry planting on raised beds. The transplant was performed for 16 treatments with plants 30 days old (02 August 1995). Composting in the final field was carried out with a dose of 90 kilograms of nitrogen per hectare as urea nitrogen source 46% of wealth was used. Urea was applied as fraccionada, the first half to 9 days after transplantation and the other half at the beginning of "EI encañado" of each line and Variety (control). The highest yield achieved that exceeded 7.0 t / ha of paddy was accomplished by the line T (PNA 1775-HU-157-5-3), with 7,690 tonnes / ha. Line T CPNA 1775-HU-157-5-3), which was also properly combined grain yield, weight of 1,000 grains, grain / straw ratio, production efficiency and battery performance, among other agronomic characteristics.